"Law-Based" and "Authorizing Norm" Conditions for Adopting a Sub-Legislative Act and Their Correlation. - Ghambaryan, Artur (Bulletin of Yerevan University C: Jurisprudence, 2024)
In this article examines the general characteristics of the "law-based" and "authorizing norm" conditions for adopting a sub-legislative act and their correlation in RA constitutional law, taking into account the existing knowledge and experience in the German and Russian doctrines on the above topic as well as the clarity of defining the cases regulated by the by-law, the method of expressing the will to adopt a by-law and the prohibition of self-authorization to adopt a by-law. The modernity of the choosen topic due to the lack of systematic interpretation of the legislative base for the adoption of a sub-legislative act by the bodies of the executive power leading to non-compliance of the corresponding terms, presence of bugs, incorrect interpretation of the functions of executive power bodies and other legal problems. As a result of the study of the topic, it can be concluded that the prohibition of self-authorization and the condition "on the basis of law" apply in the RA legal system, and the adoption of a sub-legislative act for the bodies of the executive power is a legal form of exercising the relevant functional powers defined by the law, which can be resolved only through acts of a normative nature.